2021
DOI: 10.1080/13683500.2021.1924636
|View full text |Cite
|
Sign up to set email alerts
|

Small Island Developing States (SIDS) COVID-19 post-pandemic tourism recovery: A system dynamics approach

Abstract: The economy of Small Island Developing States (SIDS) is highly dependent on tourism and travel sector. Under the impact of COVID-19, these islands have suffered strongly. Possible recovery strategies are tested through exploring the concept of risk perception as an important factor to influence the behaviour intention under the framework of theory of planned behaviour (TPB). A behavioural simulation is built to help evaluate tourism policies. This paper takes Maldives as an example. Four strategies are tested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 44 publications
0
39
0
Order By: Relevance
“…There are six island nations in the African continent: Cabo Verde, Comoros, Madagascar, Mauritius, São Tomé e Príncipe, and Seychelles, five of which belong to the Small Island Developing States (SIDS) [14]. Aside from Madagascar, which has a relatively large land area and population size, allare small countries characterized by small populations, remoteness, dependence on international trade, strong tourism and fishing industries, limited resources due to their small economies, and vulnerability to external global financial shocks [15][16][17][18]. Moreover, they also face limitations regarding access to healthcare services [19].…”
Section: African Islands Backgroundmentioning
confidence: 99%
“…There are six island nations in the African continent: Cabo Verde, Comoros, Madagascar, Mauritius, São Tomé e Príncipe, and Seychelles, five of which belong to the Small Island Developing States (SIDS) [14]. Aside from Madagascar, which has a relatively large land area and population size, allare small countries characterized by small populations, remoteness, dependence on international trade, strong tourism and fishing industries, limited resources due to their small economies, and vulnerability to external global financial shocks [15][16][17][18]. Moreover, they also face limitations regarding access to healthcare services [19].…”
Section: African Islands Backgroundmentioning
confidence: 99%
“…The outcome of the study has multiple practical implications. First, the Travel Bubble strategy is probed as a better strategy than social distancing, tax reduction strategy and joint strategy for the post pandemic tourism recovery in Small Island Developing States (SIDS) (Gu et al, 2021). So, SHT can be offered to LED countries in Africa and Asia Pacific enriched.…”
Section: Discussionmentioning
confidence: 99%
“…In order to effectively deal with the tourism crisis and restore the market, some scholars have suggested relevant strategies and suggestions. Gu et al [22] adopted a system dynamics method to test the recovery effects of social distancing, tax reduction, travel bubbles, and joint strategies on the tourism market in the post-COVID-19 context. The results showed that the most effective strategy to change tourist behaviour intentions was the travel bubble strategy.…”
Section: Literature Review 21 Tourism Crisis Management and Recovery Strategymentioning
confidence: 99%
“…Through a literature review, Li [34] found that the benefits of price discounts in scenic spots can effectively offset tourists' perception of their own tourism risks, and the price promotion of well-known scenic spots immediately creates higher attractiveness. Gu et al [22] found that the price strategy of tourism departments, by reducing tax on goods and services, can effectively increase the number of tourists. Laarman and Gregersen [35] also stated that the government, through price control, subsidies, etc., can confine the overall travel expenses of tourists within a certain range, which can help attract more tourists quickly in the short-term.…”
Section: Literature Review 21 Tourism Crisis Management and Recovery Strategymentioning
confidence: 99%